PERFORMANCE AND CARCASS EVALUATION OF BROILER CHICKENS FED DIFFERENT COMMERCIAL DIETS - Haruna, M.; Doma, U. D.; Bello, K. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
An experiment was carried out to determine the utilization of five selected commercial broiler chicken diets by broilers. Three hundred day-old chicks were randomly allotted to five diets in replicates of three containing 20 birds each in a Completely Randomized Design. Feed and water were supplied ad libitum and the feeding trial lasted for six weeks. Results for overall performance, indicated that daily feed intake was higher (P<0.05) on diets A (103.00 g), D (101.79 g) E (100.18 g) and B (96.06 g) which were the same and lower on diet C85.21 g) while daily weight gain and feed conversion ratio assumed the same trend as daily feed intake. Carcass evaluation showed a higher (P<0.05) dressing percentage on diet D (76.72 %) and lowest on diet C (67.96 %). It was therefore concluded that diets D and A gave higher dressing percentages, hence recommended for broiler chicken farmers in the study area.